A Pseudolite Indoor Wide-Area Networking Technology Based on Signal Multilevel Features. (21st August 2022) - Zhang, Heng; Yu, Baoguo; Pan, Shuguo; Sheng, Chuanzhen; Lu, Huang; Li, Yaning
Abstract : At present, pseudosatellite navigation and positioning technology is the only positioning technology compatible with GNSS navigation signals and applied to indoors. This technology can realize continuous indoor and outdoor positioning services for mobile terminals and dedicated terminals. At the same time, the indoor application of pseudolite technology also faces some problems. Aiming at the large-area networking problem of pseudolites in indoor space, this paper uses the existing indoor array pseudolite technology to propose a technique for constructing a network using the characteristics of pseudolite signals in indoor space. By making full use of the signal's multiple access classification characteristics and the signal's Doppler, interstation delay, and other characteristics, a multilevel grid segmentation and networking scheme for indoor space based on pseudolites is realized. This method combines the existing experimental foundation and experience accumulation, has the feasibility of realizing large-area networking indoors, can solve the problems faced in the current indoor pseudolite networking process, and provides guarantee for the application of pseudolite networking in indoor environments.